Immunopathogenic and clinical implications of advanced tissue analysis in non-tuberculous mycobacterial infections in children - Seidl, Maximilian; Haghighi, Elham Bavafaye; Lösslein, Anne Kathrin; Hufnagel, Markus; Lohrmann, Florens; Schneider, Christian; Kohlfürst, Daniela S.; Zenz, Werner; Gorkiewicz, Gregor; Feiterna-Sperling, Cornelia; Krüger, Renate; Bronsert, Peter; et al. (Frontiers in Immunology, 2025)
ObjectivesInfections with non-tuberculous mycobacteria (NTM) in children usually affect the lymph nodes and surrounding tissue. Although the infection is typically self-limiting, it carries a substantial risk of complications due to persistent inflammation and invasive therapeutic interventions. Yet, the immunopathogenesis of the disease is obscure, as are biomarkers guiding treatment decisions.MethodsIn this observational study, we analyzed histological samples collected in the NTMkids study to identify parameters associated with impaired wound healing and complicated disease progression. Samples from 33 patients (median age at first presentation 33 months) were investigated, with two consecutive biopsies in 9 patients.ResultsGerminal centers, a scattered distribution of granuloma associated CD4+ T-cells, higher CD8+ T-cell density inside the necrosis and foamy epitheloid cells were associated with a favorable outcome. Tissue damage presenting clinically as liquefaction was associated with an adverse outcome.ConclusionsThe identified tissue reaction patterns in NTM infections provide insights into the biology of NTM lymphadenitis in children and may aid in more precise treatment decisions.